Implementasi Reward dan Punishment dalam Membentuk Kedisiplinan Peserta Didik - Sinta Yuli Yeni; Rio Alfansyah (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
The application of rewards and punishments has an important role in shaping student discipline. Discipline is one of the factors that support the process of teaching and learning activities to be effective. This paper discusses the form, implications, and application of rewards and punishments in shaping the discipline of students of Madrasah Diniyah HM Al Mahrusiyah Putri Lirboyo Kediri. The results of this study found that the process of applying reward and punishment in madrasah diniyah with effect. The forms of rewards given vary including, praise, gifts, award certificates, while the forms of punishment given include, reprimands, white cards, yellow cards, red cards, standing in other classes. The implication of the application of reward and punishment is that participants become motivated to behave in accordance with the rules of madrasah diniyah. From the process and form of application of rewards and punishments given to students gradually and has implications for motivating students to obey the rules.The application of rewards and punishments has an important role in shaping student discipline. Discipline is one of the factors that support the process of teaching and learning activities to be effective. This paper discusses the form, implications, and application of rewards and punishments in shaping the discipline of students of Madrasah Diniyah HM Al Mahrusiyah Putri Lirboyo Kediri. The results of this study found that the process of applying reward and punishment in madrasah diniyah with effect. The forms of rewards given vary including, praise, gifts, award certificates, while the forms of punishment given include, reprimands, white cards, yellow cards, red cards, standing in other classes. The implication of the application of reward and punishment is that participants become motivated to behave in accordance with the rules of madrasah diniyah. From the process and form of application of rewards and punishments given to students gradually and has implications for motivating students to obey the rules.